Cytokines secreted from bone marrow-derived mesenchymal stem cells promote apoptosis of CD34+ leukemic stem cells as anti-cancer therapy - Raheleh Farahzadi; Ezzatollah Fathi; Somayeh Vandghanooni; Behnaz Valipour (Regenerative Therapy)
Objective: The effect of mesenchymal stem cells (MSCs) on the immortal characteristics of malignant cells, particularly hematologic cancer cells, remains a topic of debate, with the underlying mechanisms still requiring further elucidation. We explored the in vitro effect of the bone marrow-derived MSCs (BM-MSCs) on CD34+ leukemic stem cells (LSCs) enriched from the KG1-a cell line by assessing apoptosis, measuring cytokine levels, and examining TERT protein expression. Additionally, the potential signaling pathways implicated in this process, such as P53, PTEN, NF-κB, ERK1/2, Raf-1, and H-RAS, were also investigated. Methods: CD34+ LSCs were enriched from the KG1-a cell line with the magnetic activated cell sorting (MACS) method. Two cell populations (BM-MSCs and CD34+ LSCs) were co-cultured on trans well plates for seven days. Next, CD34+ LSCs were collected and subjected to Annexin V/PI assay, cytokine measurement, and western blotting. Results: BM-MSCs caused a significant increase in early and late apoptosis in the CD34+LSCs. The significant presence of interleukin (IL)-2 and IL-4 was evident in the co-cultured media. In addition, BM-MSCs significantly increased the protein expression of P53, PTEN, NF-κB, and significantly decreased p-ERK1/2, Raf-1, H-RAS, and TERT. Conclusion: The mentioned effects of IL-2 and IL-4 cytokines released from BM-MSCs on CD34+ LSCs as therapeutic agents were applied by the components of P53, PTEN, NF-κB, p-ERK1/2, Raf-1, and H-RAS signaling pathways.